The Application of Ra’yu and Istihsan in the Settlement of Marital Property in Modern Times: A Normative Study of the Principle of Proportional Justice - Muhammad Ridho Rahman; Nuril Khasyi'in (Syarah: Jurnal Hukum Islam dan Ekonomi, 2026)
The issue of the division of marital property has become increasingly complex as economic relations between husbands and wives have changed, with contributions from both parties whether economic or non-economic—not always being equal. Normative provisions that emphasize an equal division often fail to fully reflect this reality, thereby potentially leading to substantive injustice. This study employs a normative legal research method with a comparative approach, analyzing the doctrine of usul al-fiqh, classical and contemporary Islamic legal thought, and relevant legislation, particularly the Compilation of Islamic Law. The results of the study indicate that ra’yu functions as a rational instrument for assessing the actual contributions of the parties during the marriage, while istihsan serves as a corrective mechanism to deviate from general principles when their application has the potential to result in injustice. The synthesis of ra’yu and istihsan provides a methodological framework that allows for the contextualization of law without disregarding the normative foundations of Sharia. The division of marital property should not be carried out mechanically and formalistically, but must be based on the principle of proportional justice that takes into account the actual contributions of each party, both economic and non-economic. The integration of ra’yu and istihsan underscores the adaptive nature of Islamic family law and provides a normative justification for the application of substantive justice in resolving disputes over marital property in Indonesia. These findings can also serve as a conceptual foundation for reforming the Compilation of Islamic Law, particularly in reformulating the provisions on the division of joint property to be more oriented toward the principle of proportional justice and the contributions of the parties.